Peirce’s influence on Haack's reflections on the nature of logic - Nakano, Anderson Luis (2021)
In her book Deviant Logic (1974), Susan Haack argued for a “pragmatist” conception of logic. This conception holds that, (i) logic is a theory on a par with other scientific theories, differing only from such theories by its degree of generality and (ii) the choice of a particular logic is to be made based on pragmatist principles, namely, economy, coherence, and simplicity. This view was contrasted, in this book, with an “absolutist” view of logic, according to which logical laws are necessary and immune to revision. Two decades later, however, Haack acknowledged, in the Introduction to an enlarged version of the same book, that she would not approach the question of the revisability of logic in the same way she did earlier. What was missing in her first book was a distinction between the question of the necessity of the laws of logic and the question of our fallibility in recognizing which are the true laws of logic and what structures are essential to representation. She also acknowledged that this change was mainly influenced by Peirce, with whose work she had “only the most superficial acquaintance twenty years ago”. In this context, this paper has two aims: (1) to show that, in Philosophy of Logics, we can find elements that reveal a tension between her early “pragmatic” views and her changing views on the nature of logic; (2) to present some hypotheses about the role Peirce may have had in this change.